As tecnologias de informação e comunicação nas reformas educativas em Portugal - Bento Silva Duarte da (Universidade do Minho, 2001)
Considering the integration of Information and Communication Technologies (ICT) in the proposal for the Primary and Secondary Curricular Reorganisation, the author will focus and reflect about Educational Reforms in Portugal since the creation of secondary school teaching (1836). The corpus of research will take into account the legislative discourse, the research carried out on the issue, as well as a case study which takes as its main focus the set-up of didactic resources/ICT in a Portuguese secondary school a school whose foundation dates back to 1836. The aim of this paper is thus to give evidence of the crucial moments of the integration of technologies in the Portuguese educational system together with an evaluation of its relevance and contribution towards the development of school and curricular organisation.